2003
DOI: 10.1073/pnas.2034966100
|View full text |Cite
|
Sign up to set email alerts
|

Topological analysis of a plant vacuolar Na + /H + antiporter reveals a luminal C terminus that regulates antiporter cation selectivity

Abstract: We conducted an analysis of the topology of AtNHX1, an Arabidopsis thaliana vacuolar Na ؉ ͞H ؉ antiporter. Several hydrophilic regions of the antiporter were tagged with a hemagglutinin epitope, and protease protection assays were conducted to determine the membrane topology of the antiporter by using yeast as a heterologous expression system. The overall structure of AtNHX1 is distinct from the human Na ؉ ͞H ؉ antiporter NHE1 or any known Na ؉ ͞H ؉ antiporter. It is comprised of nine transmembrane domains and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
131
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 42 publications
4
131
0
5
Order By: Relevance
“…Analyses of the transcriptional profile of AtNHX1 insertional knockout mutant plants growing in the absence and presence of salt (14) revealed changes in gene expression supporting the notion that, as in the yeast ortholog Nhx1p (15), AtNHX1 plays a significant role in protein trafficking and protein targeting, probably via the regulation of intravesicular acidic pH (16). Topological analyses revealed that, whereas the N terminus of AtNHX1 is facing the cytosol, almost the entire C-terminal hydrophilic region of the protein resides in the vacuolar lumen (17). Moreover, the deletion of the C terminus of AtNHX1 doubled the Na ϩ ͞K ϩ selectivity ratio of the antiporter, suggesting a regulatory role of the C terminus of the antiporter (17).…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…Analyses of the transcriptional profile of AtNHX1 insertional knockout mutant plants growing in the absence and presence of salt (14) revealed changes in gene expression supporting the notion that, as in the yeast ortholog Nhx1p (15), AtNHX1 plays a significant role in protein trafficking and protein targeting, probably via the regulation of intravesicular acidic pH (16). Topological analyses revealed that, whereas the N terminus of AtNHX1 is facing the cytosol, almost the entire C-terminal hydrophilic region of the protein resides in the vacuolar lumen (17). Moreover, the deletion of the C terminus of AtNHX1 doubled the Na ϩ ͞K ϩ selectivity ratio of the antiporter, suggesting a regulatory role of the C terminus of the antiporter (17).…”
mentioning
confidence: 59%
“…N terminus and C terminus 3xFLAG-tagged AtCaM15 constructs were generated by a fusion PCR method (17) and cloned into the SpeI and PstI site of p425GPD and p425CYC1 plasmids (American Type Culture Collection). The resulting constructs were transformed into the yeast strain W303-1B (MAT␣ ura3-1 leu2-3,112 his3-11,15 trp1-1 ade2-1 can1-100) independently.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations